Adrenal incidentaloma: Prevalence and evaluation. Experiences from a single health network - Mitchell Munnings; Shaun Koh; Christopher Gilfillan (Endocrine and Metabolic Science)
Background: Increasing utilization and sensitivity of radiological imaging has led to an increase in the detection of adrenal incidentalomas (AIs). Most AIs are non-functional benign lesions, though, exclusion of functional and/or malignant AIs is mandatory. International guidelines describe the recommended evaluation of these lesions. However, data on local adherence to such recommendations is unknown. Aims: To investigate the prevalence and evaluation of AIs discovered in a metropolitan health network and compare the data with established guidelines. Methods: The study involves a retrospective identification of patients over 18 years old using keyword search criteria within radiology reports from computed tomography (CT) studies performed during 2019 and 2020. Clinical notes and the electronic medical record were interrogated to gather pathology results, co-morbidities, and follow-up. Patients with a known history of active malignancy, suspected adrenal pathology, or an established history of an adrenal adenoma were excluded. Results: Adrenal incidentalomas were identified in 274 patients, with a prevalence of 0.7 %. Biochemical evaluation occurred in 15.3 % of AIs, and the recommended evaluation of cortisol and catecholamine excess occurred in 8.0 % of cases. Dedicated adrenal imaging occurred in 14.6 % of cases, and 10.2 % of AIs referred to endocrinology. Benign non-functional adenoma was the most common diagnosis; however, most AIs (82.1 %) did not have a final diagnosis. Conclusions: Our study demonstrates a significant gap between guideline-recommended investigation of AIs and clinical practice. A similar suboptimal investigation rate has been reported internationally, leading to a hypothesis that is not an isolated finding. These data suggest an essential area for education to improve patient care.